Genomic assessment in Lactobacillus plantarum links the butyrogenic pathway with glutamine metabolism. Issue 1 (December 2017) - Botta, Cristian; Acquadro, Alberto; Greppi, Anna; Barchi, Lorenzo; Bertolino, Marta; Cocolin, Luca; Rantsiou, Kalliopi
Abstract The butyrogenic capability ofLactobacillus (L .)plantarum is highly dependent on the substrate type and so far not assigned to any specific metabolic pathway. Accordingly, we compared three genomes ofL. plantarum that showed a strain-specific capability to produce butyric acid in human cells growth media. Based on the genomic analysis, butyric acid production was attributed to the complementary activities of a medium-chain thioesterase and the fatty acid synthase of type two (FASII). However, the genomic islands of discrepancy observed between butyrogenicL. plantarum strains (S2T10D, S11T3E) and the non-butyrogenic strain O2T60C do not encompass genes of FASII, but several cassettes of genes related to sugar metabolism, bacteriocins, prophages and surface proteins. Interestingly, single amino acid substitutions predicted from SNPs analysis have highlighted deleterious mutations in key genes of glutamine metabolism inL. plantarum O2T60C, which corroborated well with the metabolic deficiency suffered by O2T60C in high-glutamine growth media and its consequent incapability to produce butyrate. In parallel, the increase of glutamine content induced the production of butyric acid byL. plantarum S2T10D. The present study reveals a previously undescribed metabolic route for butyric acid production inL. plantarum, and a potential involvement of the glutamine uptake in its regulation.